Expression of high-mobility group box-1 in eutopic/ectopic endometrium and correlations with inflammation-related factors in adenomyosis - Xiu-Ni Liu; Zhong-Ping Cheng (Taylor & Francis Group, 2023)
Objective To investigate the expression of HMGB1 and toll-like receptor 4 (TLR4) in adenomyosis eutopic/ectopic endometrium.Methods Twenty patients with adenomyosis and 20 controls, all undergoing laparoscopy, were recruited from September 2015 to July 2016. Samples were collected from the endometrium without adenomyosis (CE), the eutopic endometrium with adenomyosis (EuE), and the ectopic endometrium with adenomyosis (EE). The mRNA and protein expression of HMGB1 and TLR4, and interleukin-6 (IL-6) and interleukin-8 (IL-8) RNA expression levels were measured.Results The average age of the adenomyosis women was 43.4 ± 5.3 years; their BMI was 23.3 ± 2.3 kg/m2. The control group included women aged 38.8 ± 9.8 years, with BMI 22.2 ± 3.4 kg/m2. The mRNA expression levels of HMGB1, TLR4, IL-6, and IL-8 in the EE and EuE groups were higher than those in the CE group (p < .01), and those in the EE group were higher than those in the EuE group (p < .01). The protein expression levels of HMGB1 and TLR4 in the EE and EuE groups were higher than those in the CE group (p < .01); they were higher in the EE group than the ones in the EuE group (p < .01). HMGB1 mRNA was significantly positively correlated with TLR4 in EuE and EC patients (r = 0.538 and r = 0.916, p < .01), as well as with IL-6 (r = 0.470 and r = 0.976, p < .01) and IL-8 (r = 0.574 and r = 0.650, p < .01).Conclusions The overexpression of HMGB1 and TLR4 in EuE and EE is positively correlated with IL-6 and IL-8 expression. The HMGB1 signaling-mediated immune-inflammatory system might be involved in the development of adenomyosis.